THE SAXAUL- HALOXYLON PLANT AND ITS MEDICINAL PROPERTIES - Gafarova Saida Mukhamadjonovna; Khalilova Feruza Mamatkulovna (Journals Park Publishing, 2023)
The article provides information about the biology, geography of the saxaul plant and its medicinal properties. Opinions on the chemical composition of the saxaul plant and its use in folk medicine are given.
Keywords: saxule, white saxaul, black saxaul, jasan saxaul, rhenium, heart, blood vessels, allergy, Haloxylon. H. Persicum, H. Ammodendron.